Commissioning and clinical implementation of the first commercial independent Monte Carlo 3D dose calculation to replace CyberKnife M6™ patient‐specific QA measurements. Issue 11 (25th October 2020) - Milder, Maaike T. W.; Alber, Markus; Söhn, Matthias; Hoogeman, Mischa S.
Abstract: Purpose: To report on the commissioning and clinical validation of the first commercially available independent Monte Carlo (MC) three‐dimensional (3D) dose calculation for CyberKnife robotic radiosurgery system® (Accuray, Sunnyvale, CA). Methods: The independent dose calculation (IDC) by SciMoCa® (Scientific RT, Munich, Germany) was validated based on water measurements of output factors and dose profiles (unshielded diode, field‐size dependent corrections). A set of 84 patient‐specific quality assurance (QA) measurements for multi‐leaf collimator (MLC) plans, using an Octavius two‐dimensional SRS1000 array (PTW, Freiburg, Germany), was compared to results of respective calculations. Statistical process control (SPC) was used to detect plans outside action levels. Results: Of all output factors for the three collimator systems of the CyberKnife, 99% agreed within 2% and 81% within 1%, with a maximum deviation of 3.2% for a 5‐mm fixed cone. The profiles were compared using a one‐dimensional gamma evaluation with 2% dose difference and 0.5 mm distance‐to‐agreement (Γ(2, 0.5)). The off‐centre ratios showed an average pass rate >99% (92–100%). The agreement of the depth dose profiles depended on field size, with lowest pass rates for the smallest MLC field sizes. The average depth dose pass rate was 88% (35–99%). The IDCs showed a Γ(2, 1) pass rate of 98%. Statistical process control detected six plans outside tolerance levels in the measurements, all of which could be attributed the measurement setup. Independent dose calculations showed problems in five plans, all due to differences in the algorithm between TPS and IDC. Based on these results changes were made in the class solution for treatment plans. Conclusion: The first commercially available MC 3D dose IDC was successfully commissioned and validated for the CyberKnife and replaced all routine patient‐specific QA measurements in our clinic.